Pineapple De' Cafe / Norazman Ali … [et al.] - Ali, Norazman; Ismail, Marzuin; Mohd Aris, Azila; Mohd Idris, Marzura; Abd. Razak, Nor Zairawathy (2000)
we done a market survey, we decided to suggest for you to make a cafeteria that produce food, drinks and beverages made from fruits. So, we suggest to you to produce food from Tropicana fruits such as pineapple, banana, papaya and others. We suggest food from Tropicana fruits because all the fruit are well known and easy to get instead of promoting local fruits. We suggest for you this business because we want you to make different cafeteria from others. This is because, the cafeteria, which were already exist, normally will specify it concept of food. For example, the Deli' France cafeteria had already specific to a Western concept and Sushi cafeteria had specific to Japanese concept. But, this fruit cafeteria do not specific its concept. It will produce any kind of food whether the Western, Japanese, Malay, Indian, Chinese or Italian styles. However, in this report proposal, we suggest you to produce food from pineapple fruits. This is because, the pineapple fruits is easy to get and it do not have season. Besides that, the pineapple fruits can make many kind of food. Therefore, we suggest to you to named the business as Pineapple De' Cafe.